Combustion adjustment experiment of over-temperature in heating surfaces for 600 MW four-wall tangentially fired boiler. (November 2022) - Xu, Chunxing; Li, Meishuang
Abstract: Over-temperature problem have been occurred at vertical water wall and platen super-heater of 600 MW four-wall tangentially fired boiler often since it is putted into production, the AGC function of the unit cannot be used properly, and the load capacity and quick variable load mode of the unit is influenced greatly. In this paper, the over-temperature mechanism of four-wall tangentially fired boiler is explained by numerical simulation firstly, then a combustion adjustment test including boiler coal pulverizing system and secondary air register optimization experiment was carried out. It is found that the cutting radius of combustion flame of four-wall tangentially fired boiler is too large to cause the high temperature flue gas brush the vertical water, which leads to the vertical water wall over-temperature. The residual rotation under the furnace arch at the outlet of the furnace still exist, leading to smoke temperature deviation on both sides of the outlet of the furnace, causing uneven heat absorption at the platen super-heater area, which leads to the platen super-heater over-temperature. The over-temperature problem of boiler heating surface is effectively controlled after the combustion adjustment test without equipment modification. The AGC function of the unit can be used properly, and the safe and economical operation of the unit have been greatly guaranteed.